There Should Not Be Shame in Sharing Responsibility: An Alternative to Mays Social Existentialist Vision - Oakberg, Timothy J. (Ethical theory and moral practice, 2016)
Some of the greatest harms perpetrated by human beingsmass murders, for exampleare directly caused by a small number of individuals, yet the full force of the transgressions would not obtain without the indirect contributions of many others. To combat such evils, Larry May (1992) argues that we ought to cultivate a sense of shared responsibility within communities. More specifically, we ought to develop a propensity to feel ashamed of ourselves when we choose to be associated with others who transgress. Grant that we ought to assume greater moral responsibility for contributing to harms that we do not directly commit. My goal is to challenge Mays claim that we should move towards a shame culture, and to argue that we ought to focus on cultivating empathy-based care and guilt instead. An established research program spearheaded by June Tangney (Tangney, Stuewig, & Mashek, 2007) has shown that individuals who are disposed to feel shame are more likely to hide from scrutiny, blame others, get angry, and become aggressive. Cultivating shame, in short, is a recipe for increasing antisocial behavior. Policies that promote feelings of empathy-based care and guilt, however, seem better designed to achieve the desired result, namely, minimizing the harms caused by groups.